Protective Effect of Vitamin E on Gastric Mucosal Injury in Rats with Biliary Obstruction - Nuh Zafer Cantürk (Canadian Journal of Gastroenterology, 2000)
Patients with liver disease display increased susceptibility to gastric mucosal damage. A role of free radicals has been suggested in the development of gastric mucosal damage in normal subjects. The effects of antioxidant vitamin E treatment on the liver and stomach in cirrhotic rats were examined. Fifty rats were divided into three groups. Cirrhosis was induced by bile duct ligation in 40 of 50 rats. Controls underwent a sham operation. Gastric mucosal lesions were produced by intragastric administration of 1 mL of 95% ethanol in all three groups. Twenty bile duct-ligated rats were injected intramuscularly with vitamin E (100 mg/kg/day). Liver and stomach histology, and stomach malondialdehyde and glutathione levels were determined. Portal hypertension was measured. Macroscopic and microscopic gastric mucosal injury were significantly greater in the control and common bile duct-ligated groups than in the vitamin E-pretreated group (P<0.05). The tissue malondialdehyde and glutathione levels were significantly decreased in the vitamin E-administrated group compared with the common bile duct-ligated group (P<0.001). Vitamin E administration may be cytoprotective for both the liver and gastric mucosa in bile duct-ligated rats.